The Effect of UTAUT3 on Interest in Using BYOND Mobile Banking by BSI with Perceived Enjoyment as a Mediating Variable an Empirical Study of Customers of Bank Syariah Indonesia KCP Batu Diponegoro - Mubarok, Rizal Zaky; Askandar, Noor Shodik; Basalamah, Muhammad Ridwan (Electronic Journal of Education, Social Economics and Technology, 2025)
This study aims to examine the influence of habit, facilitating conditions, and personal innovativeness in IT (Information Technology) on the intention to use the BYOND by BSI mobile banking application, with perceived enjoyment serving as a mediating variable. The theoretical framework is on the extended UTAUT3 (Unified Theory of Acceptance and Use of Technology) framework, integrating psychological and affective aspects of user experience within the context of Islamic digital banking. A quantitative explanatory approach was employed using the Partial Least Squares Structural Equation Modeling (SEM-PLS) method. The study involved 200 active customers of Bank Syariah Indonesia (BSI) KCP Batu Diponegoro branch, selected through purposive sampling. Data were collected through a questionnaire employing a five-point Likert scale. The results indicate that habit and facilitating conditions significantly influence perceived enjoyment, whereas personal innovativeness in IT has no significant effect. Furthermore, habit and personal innovativeness in IT have significant direct effects on intention to use, while facilitating conditions do not. Importantly, perceived enjoyment mediates the relationship between the three independent variables and intention to use, highlighting the crucial role of positive emotional experiences in sustaining the adoption of Islamic mobile banking services. The study contributes to the extension of UTAUT3 by emphasizing the affective dimension in technology acceptance within Islamic finance. Practically, it offers strategic insights for Bank Syariah Indonesia to enhance user-centered digital experiences that foster loyalty and engagement with BYOND as an Islamic financial super-app.